Microbial Response to Fungal Infection in a Fungus-Growing Termite, Odontotermes formosanus (Shiraki) - Chen-Yu Wu (Frontiers Media S.A., 2021)
The crosstalk between gut microbiota and host immunity has emerged as one of the research foci of microbiome studies in recent years. The purpose of this study was to determine how gut microbes respond to fungal infection in termites, given their reliance on gut symbionts for food intake as well as maintaining host health. Here, we used Metarhizium robertsii, an entomopathogenic fungus, to infect Odontotermes formosanus, a fungus-growing termite in the family Termitidae, and documented changes in host gut microbiota via a combination of bacterial 16S rDNA sequencing, metagenomic shotgun sequencing, and transmission electron microscopy. Our analyses found that when challenged with Metarhizium, the termite gut showed reduced microbial diversity within the first 12 h of fungal infection and then recovered and even surpassed pre-infection flora levels. These combined results shed light on the role of gut flora in maintaining homeostasis and immune homeostasis in the host, and the impact of gut flora dysbiosis on host susceptibility to infection.